Giant Faraday rotation in single- and multilayer graphene - Crassee, Iris; Levallois, Julien; Walter, Andrew L; Ostler, Markus; Bostwick, Aaron; Rotenberg, Eli; Seyller, Thomas; van der Marel, Dirk; Kuzmenko, Alexey B (arXiv.org, 2010)
Optical Faraday rotation is one of the most direct and practically important manifestations of magnetically broken time-reversal symmetry. The rotation angle is proportional to the distance traveled by the light, and up to now sizeable effects were observed only in macroscopically thick samples and in two-dimensional electron gases with effective thicknesses of several nanometers. Here we demonstrate that a single atomic layer of carbon - graphene - turns the polarization by several degrees in modest magnetic fields. The rotation is found to be strongly enhanced by resonances originating from the cyclotron effect in the classical regime and the inter-Landau-level transitions in the quantum regime. Combined with the possibility of ambipolar doping, this opens pathways to use graphene in fast tunable ultrathin infrared magneto-optical devices.